Donation Raising Application Using Rapid Application Development (RAD) Method Based on Mobile Application - Nugraha, Aditya Bagas; Widodo, Tri (JISA(Jurnal Informatika dan Sains), 2024)
Indonesia is one of the countries that has a high social spirit in doing gotong royong. Its people love to help and build social welfare. There are several activities that prioritize the principle of gotong royong in society, one of which is donation-raising activities. Many institutions still collect donations in a conventional way. This can be an obstacle for donors because not all institutions or communities that collect funds are in the same area and the reach is relatively small. Lack of public trust is also a reason because of the rampant fraud on behalf of institutions and foundations, so that it can hamper the raising of donations. To overcome these problems, a new system is needed that can be applied to the community. A fundraising platform is needed to make it easier for people to donate easily and efficiently. The Rapid Application Development (RAD) method is used in its development. System development uses the Kotlin programming language and uses a realtime Firebase database to manage the data. With this system, the mobile application can facilitate and provide access to the community in making donations online without collecting manually, raising donations can also provide a wider range of donations.